Indirect evolution of social fitness inequalities and facultative social exploitation - Nair, Ramith R. (Proc Biol Sci, 2018)
Microbial genotypes with similarly high proficiency at a cooperative behaviour in genetically pure groups often exhibit fitness inequalities caused by social interaction in mixed groups. Winning competitors in this scenario have been referred to as ‘cheaters’ in some studies. Such interaction-specific fitness inequalities, as well as social exploitation (in which interaction between genotypes increases absolute fitness), might evolve due to selection for competitiveness at the focal behaviour or might arise non-adaptively due to pleiotropy, hitchhiking or genetic drift. The bacterium Myxococcus xanthus sporulates during cooperative development of multicellular fruiting bodies. Using M. xanthus lineages that underwent experimental evolution in allopatry without selection on sporulation, we demonstrate that interaction-specific fitness inequalities and facultative social exploitation during development readily evolved indirectly among descendant lineages. Fitness inequalities between evolved genotypes were not caused by divergence in developmental speed, as faster-developing strains were not over-represented among competition winners. In competitions between ancestors and several evolved strains, all evolved genotypes produced more spores than the ancestors, including losers of evolved-versus-evolved competitions, indicating that adaptation in non-developmental contexts pleiotropically increased competitiveness for spore production. Overall, our results suggest that fitness inequalities caused by social interaction during cooperative processes may often evolve non-adaptively in natural populations.